2011
DOI: 10.1111/j.1439-0272.2010.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in the seminal plasma and its effects on fertilisation rates in an IVF cycle

Abstract: Cytokines are released by various immunocompetent cell subsets in the male urogenital tract and are thought to affect sperm cell function and reproductive process. The aim of the study was to evaluate the levels and a possible role of seven seminal plasma cytokines with fertilisation rates in men attending an in vitro fertilisation (IVF) programme. A total of 36 men of couples who were undergoing traditional IVF in a regional reproductive medicine unit were recruited into this prospective study. Cytokines such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…16,31,32 In contrast, the concentration of INF-γ, MDC, IL-8 and TGF-β3 are apparently lower in boar SP than in human SP. 16,19,23 Whether these differences simply represent species differences or whether they have a relationship to physiological events in the male or the female, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,31,32 In contrast, the concentration of INF-γ, MDC, IL-8 and TGF-β3 are apparently lower in boar SP than in human SP. 16,19,23 Whether these differences simply represent species differences or whether they have a relationship to physiological events in the male or the female, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 For instance, to the best of our knowledge, only few cytokines have been identified in boar SP, namely the transforming growth factor-β (TGF-β) 1 and 2, interferon-γ (IFN-γ) and correlations with sperm quality and fertility. 22,23 Whether the boar SP possess a similarly full battery of cytokines remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the diagnostic value of seminal leukocytes has been questioned [25,26] . The role of many proinflammatory cytokines has been intensively investigated in male accessory gland inflammation, although their relationship with semen parameters has not been fully clarified [27][28][29] . We have recently reported that suPAR may represent a specific and sensitive marker to be used in clinical practice for the diagnosis of accessory gland inflammation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Цілком зрозуміло, що під час запального процесу в урогенітальному тракті чоловіків вміст цитокінів і біологічних активних речовин, що регулюють їх функціональну активність зазнають певних змін. У чоловіків з наявніс-тю хронічої урогенітальної інфекції було за-реєстровано суттєве зростання концентрації низки цитокінів -IЛ-1β, IЛ-5, IЛ-6, IЛ-13, IЛ-15, IЛ-17, IЛ-23, ІФН-α, моноцитарного хемотаксичного фактора (МХФ) та меншою мірою -IЛ-2, IЛ-10, IЛ-12, IЛ-18, ФНП-α, ІФН-γ [14]. Підвищений вміст цих медіато-рів запалення вказує на залучення імунних факторів для захисту чоловічого генітального тракту.…”
Section: вступunclassified